Hands-On Enterprise Automation with Python : Automate Common Administrative and Security Tasks with Python. - Aly, Bassem (Packt Publishing Ltd, 2018)
In the coming years Python programming has developed massively in terms of automation. Enterprise automation with Python will teach you how simple Python programming can make your life easier with automating your infrastructure.